Pelatihan Pembinaan Penulisan Karya Ilmiah dan Esai bagi Guru SMA/SMK/MA dalam Upaya Meningkatkan Literasi Siswa - Ari Kusmiatun; Mawaidi Mawaidi; Eko Triono; Dwi Hanti Rahayu (GUYUB: Journal of Community Engagement, 2024)
Writing training at the high school level in Yogyakarta has been going well. However, there are many problems in its implementation due to the lack of competitive motivation among teachers or school institutions. This lack of motivation causes teachers' self-confidence to decrease and students are not optimal in the process of increasing literacy. This article is the output of writing training in schools for SMA/SMK/MA teachers in an effort to increase student literacy which can create motivation for students to think critically and achieve. By using a participatory action research approach, this community (PKM) seeks to overcome demotivation regarding the ability to write scientific papers and essays at the high school level in Yogyakarta which is caused by many students who are not interested and are less competitive in the field of writing. The results of PKM that have been achieved are increased motivation of teachers and students’ writing abilities, especially in the context of writing and presentation competitions. This PKM has also succeeded in creating collaboration between institutions, both between schools and between private institutions, which will be managed in the future in the context of developing writing and increasing student literacy.